Mesoporous Silica Nanoparticles Modified inside and out for ON:OFF pH-Modulated Cargo Release - José L. M. Gonçalves; Ana Beatriz C. Lopes; Carlos Baleizão; José Paulo S. Farinha (MDPI AG, 2021)
Highly efficient pH-modulated cargo release was achieved with a new hybrid nanocarrier composed of a mesoporous silica core with functionalized pores and a grafted pH-responsive crosslinked polymer shell of 2-(diisopropylamino)ethyl methacrylate (pKa ≈ 6.5). The retention/release performance of the system was optimized by a novel approach using selective functionalization of the silica pores to tune the carrier-cargo interaction and by tunning the amount of grafted polymer. The system features excellent retention of cationic cargo at low pH and a burst release at higher pH. This results from the expanded-collapsed conformation transition of the pH-responsive polymer shell and the simultaneous change in the interaction between the cargo and the polymer shell and the modified pore walls. At low pH, the electrostatic interaction of the cationic cargo with the protonated amine groups of the extended polymer shell retains the cargo, resulting in very low leakage (OFF state). At high pH, the electrostatic interaction with the cargo is lost (due to deprotonation of the polymer amine groups), and the polymer shell collapses, squeezing out the cargo in a burst release (ON state). Pore functionalization in combination with the stimuli-responsive polymer shell is a very promising strategy to design high-performance ON:OFF smart hybrid nanocarriers for stimuli-actuated cargo release, with great potential for application in the controlled release of drugs and other biologically active agents.